2012
DOI: 10.1007/s00192-012-2004-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of urinary and fecal incontinence in Chinese women during and after their first pregnancy

Abstract: The prevalence of SUI, UUI, and FI were 25.9 %, 8.2 %, and 4.0 %, respectively, 12 months after delivery. Vaginal delivery, antenatal SUI, and UUI were associated with SUI; antenatal UUI and increasing maternal BMI at the first trimester were associated with UUI. Antenatal FI was associated with FI. Pregnancy, regardless of route of delivery and obstetric practice, had an effect on UI and FI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 29 publications
6
45
1
Order By: Relevance
“…Besides ethnicity, maternal age has been found to be an independent factor for anterior compartment descent in this study. This may explain our previous finding of a higher prevalence of antenatal urinary incontinence than in a group of similar ethnicity but lower age. It is of course highly likely that mobility of the bladder neck does not fully explain the pathophysiology of urinary incontinence.…”
Section: Discussionmentioning
confidence: 76%
“…Besides ethnicity, maternal age has been found to be an independent factor for anterior compartment descent in this study. This may explain our previous finding of a higher prevalence of antenatal urinary incontinence than in a group of similar ethnicity but lower age. It is of course highly likely that mobility of the bladder neck does not fully explain the pathophysiology of urinary incontinence.…”
Section: Discussionmentioning
confidence: 76%
“…[1][2][3][4][5][6] Several studies have shown that women are reluctant to seek help for incontinence. [7][8][9] In the Norwegian EPINCONT study, only 25% of community-dwelling women with urinary incontinence had consulted a doctor regarding their symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, pelvic floor dysfunction is two times more common in women with urinary incontinence during pregnancy and shortly after delivery (22). Chan et al stated that prevalence of stress urinary incontinence, urge urinary incontinence and fecal incontinence were 25.9%, 8.2% and 4.0% respectively after one year of delivery (23). There is a scarcity of data available about the effect of urinary and fecal incontinence following pregnancy on female sexual function.…”
Section: Discussionmentioning
confidence: 99%